2020
DOI: 10.3389/fmicb.2020.01607
|View full text |Cite|
|
Sign up to set email alerts
|

Endophytic Fungi Activated Similar Defense Strategies of Achnatherum sibiricum Host to Different Trophic Types of Pathogens

Abstract: It is well documented that Epichloë endophytes can enhance the resistance of grasses to herbivory. However, reports on resistance to pathogenic fungi are limited, and their conclusions are variable. In this study, we chose pathogenic fungi with different trophic types, namely, the biotrophic pathogen Erysiphales species and the necrotrophic pathogen Curvularia lunata, to test the effects of Epichloë on the pathogen resistance of Achnatherum sibiricum. The results showed that, compared to Erysiphales species, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 76 publications
1
19
0
Order By: Relevance
“…The induction of host plant defences by Epichloë and the production of nonalkaloid compounds with putative biological activity (e.g. epichloëcyclins) could complement the resistance provided by Epichloë ‐derived alkaloids (Pańka et al ., 2013; Johnson et al ., 2015; Shi et al ., 2020). For example, L. perenne plants associated with E. festucae var.…”
Section: Ecological Benefits and Limits Of The Endophyte‐mediated Lack Of A Plant Growth–defence Trade‐offmentioning
confidence: 99%
See 2 more Smart Citations
“…The induction of host plant defences by Epichloë and the production of nonalkaloid compounds with putative biological activity (e.g. epichloëcyclins) could complement the resistance provided by Epichloë ‐derived alkaloids (Pańka et al ., 2013; Johnson et al ., 2015; Shi et al ., 2020). For example, L. perenne plants associated with E. festucae var.…”
Section: Ecological Benefits and Limits Of The Endophyte‐mediated Lack Of A Plant Growth–defence Trade‐offmentioning
confidence: 99%
“…For example, L. perenne plants associated with E. festucae var. lolii increased the plant concentration of protective phenolic compounds, which seemed to enhance the plant’s resistance against Fusarium poae (Pańka et al ., 2013; see also Shi et al ., 2020). Plant tolerance to herbivory is an alternative defence mechanism to plant resistance (yet not mutually exclusive).…”
Section: Ecological Benefits and Limits Of The Endophyte‐mediated Lack Of A Plant Growth–defence Trade‐offmentioning
confidence: 99%
See 1 more Smart Citation
“…These fungal symbionts complement host plant defences by producing bioactive alkaloids that confer protection against a broad range of vertebrate and invertebrate herbivores [ 8 , 9 ]. Additionally, it has been recently reported that Epichloë symbionts can also induce the activation of plant SA and/or JA signalling pathways [ 10 , 11 ]. The activation of these plant defensive signalling pathways by beneficial symbionts can sometimes increase the levels of resistance of plants against certain attackers, including pathogens [ 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been recently reported that Epichloë symbionts can also induce the activation of plant SA and/or JA signalling pathways [ 10 , 11 ]. The activation of these plant defensive signalling pathways by beneficial symbionts can sometimes increase the levels of resistance of plants against certain attackers, including pathogens [ 6 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%